Prices, Location, Store Atmosphere and Promotions On Buying Interests at Maju Bersama Medan Mall: Prices, Location, Store Atmosphere and Promotions On Buying Interests at Maju Bersama Medan Mall - Fenny Krisna Marpaung; Andrian Chandra Simin; Chyntia Hilda; Derrick Darma Yuniharta; Hardy Hardy; Vincent Vincent (Institute of Computer Science (IOCS), 2020)
This study aims to determine the effect of price, location, store atmosphere and promotion on buying interest at Maju Bersama Medan Mall. This type of research is explanatory research. The entire population is 26,645 consumers who have made purchases during the 2019 period. Due to the large number of population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 10% so that there are as many as 100 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that price, location, store atmosphere and sales promotion partially or simultaneously have a positive and significant effect on consumer buying interest at Maju Bersama Medan Mall. Based on the results of this study, the implications for management are to further improve pricing for each product, determine a better location, update the store atmosphere to make it look attractive and provide even more attractive promotions.